2023
DOI: 10.3349/ymj.2022.0608
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Household Transmission of SARS-CoV-2 B.1.1.529 (Omicron) Variant from Children, South Korea, 2022

Abstract: The role that children play in the transmission of the omicron variant is unclear. Here we report an outbreak that started in young children attending various pediatric facilities, leading to extensive household transmission that affected 75 families with 88 confirmed case-patients in 3 weeks. Tailored social and public health measures directed towards children and pediatric facilities are warranted with the emergence of highly transmissible omicron variant to mitigate the impact of coronavirus diseases 2019 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thirty-one studies [ 29 – 59 ] were included in this review (Table S 1 ). Studies included 17 research articles [ 29 , 32 , 34 , 35 , 40 , 42 , 43 , 45 – 48 , 50 , 53 55 , 57 , 59 ], eight brief communications [ 30 , 31 , 33 , 36 , 39 , 51 , 52 , 58 ], three letters [ 37 , 38 , 41 ], and three reports [ 44 , 49 , 56 ]. Studies were from Belgium [ 33 ], Brazil [ 37 ], China [ 34 36 , 42 , 44 , 45 , 49 51 , 53 57 , 59 ], Germany [ 29 ], Japan [ 46 ], Netherlands [ 30 ], Singapore [ 38 , 52 ], South Korea [ 32 , 39 41 , 58 ], Spain [ 31 ], U.K. [ 47 ], and U.S.A. [ 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one studies [ 29 – 59 ] were included in this review (Table S 1 ). Studies included 17 research articles [ 29 , 32 , 34 , 35 , 40 , 42 , 43 , 45 – 48 , 50 , 53 55 , 57 , 59 ], eight brief communications [ 30 , 31 , 33 , 36 , 39 , 51 , 52 , 58 ], three letters [ 37 , 38 , 41 ], and three reports [ 44 , 49 , 56 ]. Studies were from Belgium [ 33 ], Brazil [ 37 ], China [ 34 36 , 42 , 44 , 45 , 49 51 , 53 57 , 59 ], Germany [ 29 ], Japan [ 46 ], Netherlands [ 30 ], Singapore [ 38 , 52 ], South Korea [ 32 , 39 41 , 58 ], Spain [ 31 ], U.K. [ 47 ], and U.S.A. [ 43 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies [ 47 , 57 ] reported mean generation time and two studies [ 51 , 54 ] reported adjusting for right truncation. Nine studies [ 29 , 30 , 38 , 41 , 42 , 47 , 48 , 50 , 58 ] were exclusively from the household setting. The study with the largest sample size [ 29 ] only reported the number of households included in the serial interval analysis rather than the number of primary/secondary case pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The vital role of children in contributing to the household transmission during Omicron wave has also been noticed. 10 These factors may have also influenced our finding that children were the index cases in more than ⅔ of the families.…”
Section: Children Being the First Covid-19 Case In The Householdmentioning
confidence: 96%
“…[7][8][9] Particularly during B.1.1.529 (Omicron) variant surge, it was demonstrated that children notably contributed to spreading the infection to their households. 10 Evaluating SARS-CoV-2 transmission is challenging. Long incubation period, a high percentage of asymptomatic cases and complex net of social interactions make it difficult to reconstruct the precise chains of transmission.…”
mentioning
confidence: 99%